PENEGAKAN HUKUM IZIN PEMBUANGAN AIR LIMBAH PADA USAHA CUCI KENDARAAN BERMOTOR DI SURABAYA - Siti Ngaisah (Pusat Riset dan Inovasi Nasional, 2022)
The state is an organization that has a purpose. The purpose of this study is to enforce the law regarding permits for waste water disposal in motor vehicle washing businesses and the sanctions imposed by the government on motorized vehicle washing businesses that do not have a waste water disposal permit. Normative juridical research, namely research originating from laws and regulations that present actual facts with the topic of study. Law enforcement of waste water disposal permits in motorized vehicle washing businesses through administrative instruments aims to prevent acts or omissions that violate the law or do not meet the requirements, stop or return to their original state (before the violation). So the focus of administrative sanctions is the actions of violators of the rules. In the Surabaya City Regional Regulation Number 12 of 2016 concerning Water Quality Management and Wastewater Control Article 34 explains the administrative sanctions referred to in the form of: written warning, Government coercion, Freezing of waste water disposal permits, Revocation of waste water disposal permits. In addition to administrative sanctions, there are also criminal sanctions in the form of violations. The local government should socialize the Regional Regulation on Water Quality Management and Wastewater Control to the general public and the organizers of motor vehicle washing wastewater management (motor vehicle washing entrepreneurs) in order to increase legal awareness embedded in the community and it is hoped that the government will issue implementing regulations, namely Regulation Mayor.